Cold plasma and carnauba wax as strategies to produce improved bi-layer films for sustainable food packaging. (November 2020) - Romani, Viviane Patrícia; Olsen, Bradley; Pinto Collares, Magno; Meireles Oliveira, Juan Rodrigo; Prentice, Carlos; Martins, Vilásia Guimarães
Abstract: Fish protein films present promising properties for use in food packaging; however, their hydrophilic behavior still limits their use. In the present study, cold plasma and a carnauba wax coating were combined as a strategy to reduce the sensitivity to water of films produced with myofibrillar proteins from fish. Bi-layer films were produced by protein solution casting, followed by plasma-treatment (glow discharge) and coating with carnauba wax. The effects of plasma and wax coating on the packaging-related properties of protein films (thickness, mechanical and barrier performance, water solubility, color and opacity), microstructure, and glass transition and melting temperatures were evaluated. The importance of cold plasma to produce bi-layer films was confirmed since inferior properties were obtained for coated samples without plasma application. The glow discharge plasma application followed by carnauba wax coating resulted in 175% higher tensile strength and 65% lower water vapor permeability of fish protein films under the best conditions identified in comparison to control films. The modifications of fish protein films properties were confirmed by the scanning electron microscopy images, X-ray diffraction pattern and thermal transitions. The combination of cold plasma and carnauba wax coating is an alternative to improve the packaging properties of fish protein films, addressing the need to reduce synthetic plastics accumulation in nature, while using environmentally friendly resources and technologies. Graphical abstract: Image 1 Highlights: Cold plasma and carnauba wax coating were applied to fish protein films. Cold plasma was used to improve films performance and increase adhesion properties. Carnauba wax was coated in fish protein films due to the its hydrophobic behavior. Plasma and wax coating increased films' tensile strength and barrier properties. The overall packaging properties of films were improved by the strategies utilized.